Glycosylation in room temperature ionic liquid using unprotected and unactivated donors - Park, T.; Weiwer, M.; Yuan, X.; Baytas, S.N.; Munoz, E.M.; Murugesan, S.; Linhardt, R.J.
Glycosylation in room temperature ionic liquid is demonstrated using unprotected and unactivated donors. Modest yields of simple benzyl glycosides and disaccharides of glucose, mannose and N-acetylgalactosamine were obtained in 1-ethyl-3- methylimidazolium benzoate with Amberlite IR-120 (H+)resin or p-toluenesulfonic acid as promoters.
Keywords: GLYCOSYLATION; ROOM TEMPERATURE IONIC LIQUIDS; UNPROTECTED DONOR; UNACTIVATED DONOR